The Effects of Islamic Economic Revitalization Discourse on Institutionalizing the Zakat Management System in Contemporary Indonesia - Moh. Abd. Rahman; Abdul Bari (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis Dan Studi Ekonomi Syariah, 2026)
This study aims to analyze the effects of Islamic economic revitalization through the discourse of institutionalizing the zakat management system in contemporary Indonesia. Zakat, as one of the pillars of Islamic economics, has great potential to improve the social and economic welfare of society. However, zakat management in Indonesia still faces challenges in terms of the effectiveness of its distribution and utilization. Using a qualitative approach, this article examines various policies that have been implemented in zakat management and the role of zakat institutions in promoting economic growth based on Islamic values. This study also discusses how revitalizing the Islamic economy can provide a solution to the economic inequality that exists in Indonesia. By establishing a more organized and institutionalized zakat management system, it is hoped that a fairer and more effective distribution system will be created, and the goal of inclusive and sustainable economic development will be achieved more quickly.